Between A Rock and A Hard Place - Ralston, Aron (London Simon & Schuster, 2004)
In April 2003, Aron Ralston, a 27-year-old outdoorsman and adventurer, set off for a day's hike through a remote part of Utah. A large rock came loose and pinned Aron's arm against the canyon wall. After five days of being trapped, Aron used the rock's hold to break his arm bones and proceeded to cut off his arm to free himself
Include Color Illustration
Keywords: Ralston, Aron -- Utah--Bluejohn Canyon -- Rock climbing accidents